A New Measure of Text Formality: An Analysis of Discourse of Mao Zedong. Issue 3 (2nd April 2016) - Li, Haiying; Graesser, Arthur C.; Conley, Mark; Cai, Zhiqiang; Pavlik, Philip I.; Pennebaker, James W.
Abstract : Formality has long been of interest in the study of discourse, with periodic discussions of the best measure of formality and the relationship between formality and text categories. In this research, we explored what features predict formality as humans perceive the construct. We categorized a corpus consisting of 1, 158 discourse samples published in the Collected/Selected Works of Mao Zedong into the following categories: conversations, speeches, letters, comments, published articles, telegrams, and official documents. We developed two models of human formality perception: one measured at the multitextual level and one at the word level. We compared these two models with the previous metrics of formality when predicting human formality judgments. The weighted formality model at multiple levels of language, discourse, and psychological features best captured the concept of formality as humans perceive it using genre (narrativity), discourse cohesion, topic-related words (e.g., embodiment), and emotional words (positive emotion and negative emotion).